Metabolic Syndrome: Addressing Health Risks among Police Officers - Sharma, Mohit; Kaur, Jaskiran; Ahi, Rajinder Singh; Jindal, Purnima; Kaur, Jaswant; Sehgal, Garima (Disease and Health Research: New Insights Vol. 6, 2024)
Lifestyle factors and stress have indeed been linked to the development of Metabolic syndrome (MetS). The transition towards industrialization often brings about changes in people's economy and lifestyle, which can contribute to the increased prevalence of noncommunicable diseases such as Cardiovascular disease (CVD) and MetS-related conditions like diabetes mellitus. Police officers have a higher prevalence of MetS compared to the general population of the same age and gender. Shift work, high levels of stress, and poor dietary habits are significantly associated with an increased risk of MetS among police officers. Targeted interventions addressing lifestyle factors, such as nutrition, physical activity, and stress management, can effectively reduce the prevalence of MetS in police officers. This chapter will give a review of the prevalence of MetS among police forces, shedding light on the specific incidence rates and factors contributing to the development of MetS within this group.